138 Endovascular Hepatic Artery Stents in The Modern Management of Post-Pancreatectomy Haemorrhage. (12th October 2021) - Finch, L M; Baltatzis, M; Byott, S; Ganapathy, A K; Kakani, N; Lake, E; Cadwallader, R; Hazar, C; Seriki, D; Butterfield, S; Jegatheeswaran, S; Jamdar, S; et al.
Abstract: Aim: Post-operative haemorrhage is a potentially lethal complication of pancreatoduodenectomy. This study reports on endovascular hepatic artery stents in the management of post-pancreatectomy haemorrhage. Method: This is a retrospective analysis of a prospectively maintained, consecutive dataset of 440 patients undergoing pancreatoduodenectomy over 68 months. Data are presented on bleeding events and outcome, contextualized by the clinical course of the denominator population. International Study Group for Pancreas Surgery (ISGPS) terminology was used for post-pancreatectomy haemorrhage. Results: Sixty-seven (15%) had post-operative haemorrhage. Fifty (75%) were male and this gender difference was significant (P = 0.001; two-proportions test). Post-operative pancreatic fistulas were more frequent in the post-operative haemorrhage group (P = 0.029; two-proportions test). The median (IQR) delay between surgery and haemorrhage was 5 (2-14) days. Twenty-six required intervention comprising re-operation alone in 12, embolization alone in 5 and endovascular hepatic artery stent deployment in 5. Four further patients underwent multiple interventions with two having stents. Endovascular stent placement achieved initial haemostasis in 5 (72%). Follow-up was for a median (IQR) of 199 (145-400) days post-stent placement. In two patients the stent remained patent at last follow-up. The remaining 5 stents occluded with a median (IQR) period of proven patency of 10 (8-22) days. Conclusions: This study shows that in the specific setting of post-pancreatoduodenectomy haemorrhage with either a short remnant GDA bleed or a direct bleed from the hepatic artery, where embolization risks occlusion with compromise of liver arterial inflow, endovascular hepatic artery stent is an important haemostatic option but is associated with a high risk of subsequent graft occlusion.